Mengucapkan Salam Dalam Pembentukan Akhlakul Karimah di Sekolah - Susrianingsih (STAI Serdang Lubuk Pakam, 2019)
Islamic teachings strongly encourage praying for one another and among the words that contain prayers are greetings. In summary assalamu'alaikum means to convey a message of peace, respect and prayer. Assalamu'alaikum warahmatullahi wabarakatuh means